Use of a Titrimetric Method to Assess the Bacterial Spoilage of Fresh Beef - Shelef, Leora A. (1970)
A new method of determining bacterial spoilage in fresh beef is presented. The technique is based upon the fact that as beef undergoes refrigerator spoilage, there is a gradual increase in the production of alkaline substances by the spoilage flora. The level of these substances was measured by titrating meat homogenates to a pH 5.00 end point, employing 0.02 n HCl and an autotitrator. When 23 samples of ground beef from retail stores were tested, an average of 1.32 ml of acid was required for titration of 1 g of fresh beef to pH 5.00, whereas 2.58 ml was required for the same meat at the onset of spoilage. Preliminary data indicate that beef which requires more than 2 ml of 0.02 n HCl/g to lower its pH to 5.00 under the conditions of the test is in some state of incipient spoilage. The statistical correlation between titration values, log bacterial numbers, and extract-release volume was high (P < 0.001). The technique is simple to execute and is highly reproducible, and duplicate samples can be run within 15 min.